2022
DOI: 10.2478/jvetres-2022-0063
|View full text |Cite
|
Sign up to set email alerts
|

Histamine content in selected production stages of fish products

Abstract: Introduction Histamine intoxication, known as scombroid fish poisoning, is caused by the consumption of foods with high levels of histamine. This biogenic amine is formed as a result of histidine decarboxylation by bacterial decarboxylases present in food, including fish and fish products. The aim of this study was to investigate the content of histamine at different production stages of canned, marinated and smoked fish. Material and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Tuna fish histamine levels are 21.1 mg N/100 g (Ariyani et al, 2004). Madejska et al, (2022) reported that smoked fish has lower histamine levels than fresh fish. Smoking fish can delay the formation of histamine in fish products (Madejska et al,2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation

Chemical and Microbiological Characteristics of Sei-Pindang Tuna Fish

I Gde Suranaya Pandit,
Pande Ayu Naya Kasih Permatananda,
I Nengah Suaria
2024
FJMR
“…Tuna fish histamine levels are 21.1 mg N/100 g (Ariyani et al, 2004). Madejska et al, (2022) reported that smoked fish has lower histamine levels than fresh fish. Smoking fish can delay the formation of histamine in fish products (Madejska et al,2022).…”
Section: Discussionmentioning
confidence: 99%
“…Madejska et al, (2022) reported that smoked fish has lower histamine levels than fresh fish. Smoking fish can delay the formation of histamine in fish products (Madejska et al,2022). Consumption of fish containing more than 100 mg/100 g of histamine can cause illness with cardiovascular symptoms (body spinning, urticaria, hypotension, and dizziness), gantroenteritis (stomach spasms, diarrhea, and vomiting), and neurological (pain and paraesthesiae) (Mc Lauchin.…”
Section: Discussionmentioning
confidence: 99%

Chemical and Microbiological Characteristics of Sei-Pindang Tuna Fish

I Gde Suranaya Pandit,
Pande Ayu Naya Kasih Permatananda,
I Nengah Suaria
2024
FJMR
“…Anna Madejska [16] провела дослідження вмісту гістаміну в 133 зразках сирої риби, 76 зразках копченої риби, 54 -риби в розсолі, 39 -рибних консервів і 18 -інших продуктів. Гістамін виявлено у 55 (17,2 %) із 320 досліджених проб, у тому числі у 8 зразках сирої риби (понад 100 мг/кг).…”
unclassified